Direct tillage system and crop rotation in the Cerrado (Research, Society and Development, 2022)
The Direct Tillage System (DTS)  is a conservationist agricultural practice capable of promoting several benefits, highlighting the improvements in the physical, chemical and biological attributes of the soil. Although it is a system that is already well established in the Cerrado, the region is still characterized mainly by soybean monoculture or succession (soybean/corn), which harms the soil and productivity in the long term. Thus, the adoption of crop rotation, with different plant species, such as cover crops, is one of the basic premises of the DTS, fundamental to maintain good soil cover and efficient nutrient cycling. In this way, the objective of the work, carried out through an exploratory bibliographic research and qualitative approach, was to bring information regarding the DTS and crop rotation to improve the Cerrado soil. Crop rotation is a viable practice to be used in agricultural cultivation areas, contributing to the improvement of soil quality, to the control of weeds, diseases and pests, reducing the need for the application of pesticides, in addition to optimizing the use of nutrients. In short, it is concluded that the implementation of the DTS in the Cerrado, respecting the basic premise of crop rotation, is a viable alternative that contributes to sustainable agricultural production in the region, in addition to being an easy-to-execute, low-cost practice that provides productive gains, if done correctly.